2006 Conference on Computer Vision and Pattern Recognition Workshop (CVPRW'06)
DOI: 10.1109/cvprw.2006.155
|View full text |Cite
|
Sign up to set email alerts
|

Peg-Free Hand Shape Verification Using High Order Zernike Moments

Abstract: Hand-based verification is a key biometric technology with a wide range of potential applications both in industry and government. The focus of this work is on improving the efficiency, accuracy, and robustness of hand-based verification. In particular, we propose using high-order Zernike moments to represent hand geometry, avoiding the more difficult and prone to errors process of hand-landmark extraction (e.g., finding finger joints). The proposed system operates on 2D hand silhouette images acquired by plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…This authentication takes into consideration the shape and geometrical details of the whole hand (Amayeh, Bebis, Erol, & Nicolescu, 2006). Length and width of the fingers, the diameter of the palm and the perimeter are examples of these geometric features.…”
Section: Hand Featuresmentioning
confidence: 99%
“…This authentication takes into consideration the shape and geometrical details of the whole hand (Amayeh, Bebis, Erol, & Nicolescu, 2006). Length and width of the fingers, the diameter of the palm and the perimeter are examples of these geometric features.…”
Section: Hand Featuresmentioning
confidence: 99%
“…The hand's geometry is not known to be very distinctive between individuals [5] and the issue of its uniqueness is still somewhat controversial [6]. Recent research studies [7,8,9] have shown high recognition rates, but the datasets used in these studies were acquired in highly controlled environments. Thus, even if the hand's geometry is unique amongst a large population, it might not be feasible to extract accurate features in a rather unconstrained environment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two, many recent works have involved increasingly higher moment orders. They include, among others, invariant image watermarking (30 orders) [24], moving object reconstruction (55 orders) [25], and hand shape verification (60 orders) [26].…”
Section: Introductionmentioning
confidence: 99%